Presentation of a Model for a Competency-Based Succession Planning Model with Respect to Adjusting Role of Organizational Culture in Telecommunication Infrastructure Company of Iran (TICIR) - Sorush Niknamian (Britain International for Academic Research (BIAR) Publisher, 2020)
The current research aims to propose a competency-based succession planning model with respect to adjusting role of organizational culture in Telecommunication Infrastructure Company of Iran (TICIR). This study was conducted as an applied research in terms of objective and it was assumed as a descriptive survey by taking approach toward interpretative structural modeling. The statistical population of this study included two groups of experts and directors (Directors general, chairmen of offices, responsible experts and experts of TICIR Company). Primarily, in order to determine sample size for statistical population, 20 of experts were elected using non-randomized and selective sampling method and 340 members of the second statistical population were chosen by means of classified sampling technique including directors general, deputies of directors general, chairmen of offices, responsible experts and other experts of TICIR Company. The findings about succession planning model indicated that the variable of succession planning reached to a level higher than satisfactory rate therefore all of the related elements were placed higher than satisfactory level. Finally variable of organizational culture, as adjusting variable, was also placed at the level higher than satisfactory rate in this study. Hence, all of these variables reached to the level higher than satisfactory rate.